A study of voltage regulation in microgrid using a DSTATCOM - Ziyaad H. Saleh; Zaid H. Ali; Raid W. Daoud; Ahmed H. Ahmed (Institute of Advanced Engineering and Science, 2020)
A well-prepared abstract enables the reader to identify the basic content. This paper presents the solution of voltage fluctuations in urgent situations by providing voltage and reactive support from a distribution static synchronous compensator (DSTATCOM) in the grid. Also, it analyses the influences of DSTATCOM as a voltage controller and compares the system performance with and without DSTATCOM. The DSTATCOM is used in the study to maintain voltage in the microgrid (MG) to be around the rated value after Microgrid disturbance. A successful simulink model of the photovoltaic (PV) system and the proposed DSTATCOM are illustrated to work together as the Microgrid. Microgrids could provide unique resilience and reliability when the environment encountered with less water, higher temperatures, more frequent and harsh wildfires, and severe weather events. The proposed DSTATCOM was installed in different locations in the MG and the best location was chosen to achieve the goal of improved power quality and efficiency. In this paper, two scenarios are discussed with and without DSTATCOM. The simulation results show the difference between the MG with and without DSTATCOM and how the DSTATCOM can amplify power quality in the Microgrid. The proposed DSTATCOM has the capability to improve dampen power oscillations during transit events.